Application of nanotechnology for enhancing photodynamic therapy via ameliorating, neglecting, or exploiting tumor hypoxia. Issue 1 (23rd March 2020) - Hu, DanRong; Pan, Meng; Yu, Yan; Sun, Ao; Shi, Kun; Qu, Ying; Qian, ZhiYong
Abstract: Photodynamic therapy (PDT), an oxygen‐dependent modality, has been clinically approved and is considered a promising approach for cancer treatment. However, PDT shows noticeable limits due to the hypoxic nature of most solid tumor microenvironments. In recent years, various strategies have been developed to overcome tumor hypoxia either via oxygen‐replenishing approaches or via diminishing oxygen dependence. Both of these approaches have shown promise in reversing hypoxia‐relevant PDT resistance and thus improve antitumor efficacy. However, the low oxygen level at the tumor site is also an opportunity for the development of new therapeutic modalities, such as hypoxia‐activated chemotherapy, hypoxia‐inducible drug release, and starvation therapy. Therefore, a combination of these therapeutic modalities with PDT could promote their synergetic efficacy. Herein, we present an overview of the recent trend in the modulation and utilization of tumor hypoxia via nanomedicine‐based strategies, followed by a summary of the design and mechanisms of these nanosystems to improve PDT. Finally, current challenges and future perspectives for how PDT can achieve more extensive clinical applications for cancer therapy are discussed. Abstract : A comprehensive review is presented on the recent progress of nanomedicine‐based strategies on intervening with tumor hypoxia for enhancing PDT efficacy. The strategies are based on three different starting point, ameliorating, neglecting, or exploiting tumor hypoxia, for a common purpose: improving PDT efficacy.